2018
DOI: 10.1007/s10549-018-4748-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the efficacy of cancer therapeutics in patient-derived xenograft models of metastatic breast cancer

Abstract: This study highlights the utility of PDX models for studying the efficacy of therapeutics in reducing metastatic burden in specific organs. The differential treatment responses between two PDX models of the same intrinsic subtype, in both the primary and metastatic setting, recapitulates the challenges faced in treating cancer patients and highlights the need for combination therapies and predictive biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 61 publications
1
31
0
Order By: Relevance
“…Cell lines have been shown to undergo considerable changes while in culture that can affect drug response, whereas three-dimensional PDX cultures have been shown to more faithfully maintain tumor cell morphology, gene expression, and drug response profiles [55][56][57] . Indeed, we have previously found that two of the breast cancer PDXs employed in the present studies maintain the gene expression profiles of their in vivo counterparts after seven days in cell culture 36 . Therefore, preclinical drug screening studies using PDXs are more likely than those using cell lines to be indicative of in vivo efficacy, and in vivo PDX drug studies are more likely to predict clinical potential 37 .…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Cell lines have been shown to undergo considerable changes while in culture that can affect drug response, whereas three-dimensional PDX cultures have been shown to more faithfully maintain tumor cell morphology, gene expression, and drug response profiles [55][56][57] . Indeed, we have previously found that two of the breast cancer PDXs employed in the present studies maintain the gene expression profiles of their in vivo counterparts after seven days in cell culture 36 . Therefore, preclinical drug screening studies using PDXs are more likely than those using cell lines to be indicative of in vivo efficacy, and in vivo PDX drug studies are more likely to predict clinical potential 37 .…”
Section: Discussionmentioning
confidence: 50%
“…For PDX cell viability assays, PDX cells were plated in 96-well plates at 25,000 cells per well in M87 medium 33 and treated with drugs for 72 h, followed by imaging and measurement of luciferase activity (total photon flux per second) two minutes after the addition of D-luciferin (15 mg/ml; GoldBio) to each well (1/10 of total volume per well), using the IVIS Spectrum In Vivo Imaging System (Xenogen IVIS-200) and living image software (PerkinElmer), as described in our previous work 36 . For cell line viability assays, MDA468, HCC1143, or HCC1937 cells were plated in 96-well plates at 5,000 cells per well in complete RPMI-1640 GlutaMAX medium, cultured overnight to allow for adherence, and subsequently treated with drugs for 72 h. Viability of cell lines was measured using the CellTiter-Glo Luminescent Viability Assay (Promega), according to the provided protocol.…”
Section: Cell Viability Assaysmentioning
confidence: 99%
“…five-fold the concentration used in the present study. Bortezomib partially reduced tumor growth in TNBC patient-derived xenografts at 0.75 mg/kg [ 51 ], i.e. three-fold the dosage used in our in vivo protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-derived xenografts (PDX) are currently considered the ''gold standard'' in modeling tumors and their microenvironment, in part because they can reflect the heterogeneity of tumor populations, and capture various host cell types (such as endothelial cells and fibroblasts) that compose the tumor microenvironment (122)(123)(124). These have become the preferred model to study drug sensitivity in tumors as well as chemotherapy and radiation resistance (125)(126)(127). PDX models are generally implanted in immunodeficient animals to prevent their rejection.…”
Section: Are Patient-derived Tumor Xenografts An Appropriate Model Fomentioning
confidence: 99%